Dokumentowanie śledztwa allewiacyjnego po gradobiciu albo powodzi w Królestwie Polskim na podstawie akt naczelników powiatu do 1866 roku - Machut-Kowalczyk, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Alleviatory investigations were conducted in 1842–1866 by heads of districts. All important actions taken after a hailstorm or a flood were documented. The records included a report or request initiating the proceedings, site inspection protocols, lists of taxes paid, income gained, correspondence etc. The last group of documents comprised protocols of oaths taken before the magistrates’ court after the harvest. Proper documentation of investigations was controlled by higher level authorities. The records are full of recommendations, instructions and orders from governor and government bodies.
Keywords: Królestwo Polskie; ulgi; ulgi podatkowe; postępowanie naprawcze